Analisis penerimaan sistem visitor counter Perpustakaan Politeknik Harapan Bersama Tegal menggunakan technology acceptance model - Nizzatur Ro'fatin Nisa (FPPTI Jawa Tengah, 2022)
Visitor counter information system is one of library automation as a form of web-based member visit record development. The visitor counter system used is the parent of SliMS 9 Bulian which was implemented at the Harapan Bersama Polytechnic Library to replace the previous version. To determine the level of acceptance of the system based on the perspective of library members, an information systems research model is needed on acceptance attitudes. The model that suits the purpose of this research is the Technology Acceptance Model (TAM) which is a model of acceptance of the information system that will be used by the user. The research method used is qualitative research methods and data collection is based on direct observation and interviews with library members (students, lecturers, and education staff). Analysis of the data obtained in this study shows that the visitor counter system at the Harapan Bersama Polytechnic Library fulfills the main aspects of TAM, namely perceived ease of use and perceived usefulness. Then based on the acceptance analysis, the visitor counter system which is the object of the study can be accepted by members of the Harapan Bersama Polytechnic Library.